Nurse prescribing practices across the globe for medication-assisted treatment of the opioid use disorder (MOUD): a scoping review - Sonam Prakashini Banka-Cullen; Catherine Comiskey; Peter Kelly; Mary Beth Zeni; Ana Gutierrez; Usha Menon (BMC, 2023)
Abstract Background Despite the dramatic increase in opioid-related deaths in recent years, global access to treatment remains poor. A major barrier to people accessing Medication-assisted treatment of the opioid use disorder (MOUD) is the lack of providers who can prescribe and monitor MOUD. According to the World Drug Report, more young people are using drugs compared with previous generations and people in need of treatment cannot get it, women most of all. Nurse prescribers have the potential to enhance both access and treatment outcomes. Nurse prescribing practices do, however, vary greatly internationally. The aim of this scoping review is to explore nurse prescribing practices for MOUD globally with a view to informing equitable access and policies for people seeking MOUD. Methods This scoping review was informed by the preferred reporting items for systematic reviews and meta-analysis extension for scoping reviews (PRISMA-ScR). Electronic searches from 2010 to date were conducted on the following databases: PsycInfo, PubMed, Embase, and CINAHL. Only studies that met the eligibility criteria and described nurse prescribing policies and/or behaviours for MOUD were included. Results A total of 22 articles were included in the review which found several barriers and enablers to nurse prescribing of MOUD. Barriers included legislation constraints, lack of professional education and training and the presence of stigmatizing attitudes. Enablers included the presence of existing supportive services, prosocial messaging, and nurse prescriber autonomy. Conclusion The safety and efficacy of nurse prescribing of MOUD is well established, and its expansion can provide a range of advantages to people who are dependent on opiates. This includes increasing access to treatment. Nurse prescribing of MOUD can increase the numbers of people in treatment from 'hard to reach' cohorts such as rural settings, or those with less financial means. It holds significant potential to reduce a wide range of harms and costs associated with high-risk opiate use. To reduce drug-related death and the global burden of harm to individuals, families, and communities, there is an urgent need to address the two key priorities of nurse prescriber legislation and education. Both of which are possible given political and educational commitment.